Knowledge, attitude, practice, and risky behaviours related to sexually transmitted infections among preparatory school students in western Addis Ababa, Ethiopia - Ketema Ayano; Takele Taye Desta; Mihiretu Kumie Takele; Endawoke Amsalu; Dagim Jirata Birri (Discover Public Health)
Abstract Background In Ethiopia, STIs (sexually transmitted infections) are among the most important diseases in the childbearing age group and adults. This study aimed to assesses the knowledge, attitudes, practices, and risky behaviours related to STIs among preparatory school students in western Addis Ababa, Ethiopia. Methods A cross-sectional study design was used in this study. A multi-sage sampling was used to select a total of 422 students from Dilachen and Addis Ketema preparatory schools. Data were collected using a pretested, structured questionnaire. The collected data were checked for completeness before analysis. The data were entered into Excel, and then exported into a Statistical Package for Social Sciences version 20 for analysis. Descriptive statistics were used to analyse variables such as age, sex and other variables. The frequency distribution of both dependent and independent variables was calculated. The summary results were presented in frequency tables and a chi-square test was used to test the association between variables. Results In this study, most respondents (89.6%) were aware of STIs, but nearly over half (54.2%) of the students did not know the types of STIs. Among those who had sexual experience, a large percentage (74.3%) did not use condoms during their first sexual intercourse, and only a few (26.6%) consistently used condoms during sexual intercourse. Some students with a history of STIs preferred non-conventional treatments such as traditional medicine or religious healings. Additionally, several students were engaged in various addictions. Statistically significant associations were found between respondents’ knowledge about the main types of STIs and their marital status and their mother’s level of education. Conclusion Most students were knowledgeable about STIs. Knowledge regarding modes of transmission, and prevention methods was significantly high, although half of them had a knowledge gap about the types and curability of STIs. Many of the students practiced unprotected sex, especially during their first sexual experience. This study highlights the need for reproductive health education and the promotion of safe sex practices among students.